If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + 2x = -2x + -5 Reorder the terms: -2 + 2x = -5 + -2x Solving -2 + 2x = -5 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -2 + 2x + 2x = -5 + -2x + 2x Combine like terms: 2x + 2x = 4x -2 + 4x = -5 + -2x + 2x Combine like terms: -2x + 2x = 0 -2 + 4x = -5 + 0 -2 + 4x = -5 Add '2' to each side of the equation. -2 + 2 + 4x = -5 + 2 Combine like terms: -2 + 2 = 0 0 + 4x = -5 + 2 4x = -5 + 2 Combine like terms: -5 + 2 = -3 4x = -3 Divide each side by '4'. x = -0.75 Simplifying x = -0.75
| x+5/8=9/4+x-7/3 | | (6x+7y)(6x+7y)=t | | 4(11.5-2)= | | 5x-1=7x+5 | | -2x-10= | | 4(m-2)=38 | | -0.6=-0.5u+0.2u | | -3w(w-4)(w+3)=t | | -6(3)=-18 | | x/12=x/13-10 | | (3x+6)(3x+6)=t | | s^2+6s=8+0 | | 6(-3)=-18 | | (x+8)(x-8)=t | | n^2-4n+7=4 | | 120-(qi+qb)=2qi | | 4(2x)+4(5)=44 | | (x+12)(x-12)=t | | 5x+5z=5 | | -12.2+6.1+15.8= | | v^2+5v=14 | | 6x+3y+4z=3 | | 6x+3y+4z=3 | | (a+b)(x-b)=x(x+b) | | 120-(q+x)=2q | | 4(x-2)-3=6x-2(5+x) | | (x-12)(x-12)=t | | (m+7)(m+7)=t | | b+(-18)= | | -8x-13x=147 | | x^2+28x-102=0 | | 9(3n-5)=(9n+2)+5 |